Program Report: Nîsohkamâtowak—Helping Patients and Families Living With Kidney Disease in Northern Saskatchewan. (January 2022) - Blair, Tiffany; Babyn, Paul; Kewistep, Gilbert; Kappel, Joanne; Stryker, Rod; Ramsden, Vivian R.; Neudorf, Cory; Levandoski, Carmen
Purpose of the Program: Nîsohkamâtowak, the Cree word for Helping Each Other, is an initiative to close gaps in kidney health care for First Nations and Métis patients, their families, and communities in northern Saskatchewan. Nîsohkamâtowak emerged from a collaboration between the Kidney Health Community Program and First Nations and Métis Health Services to find ways to deliver better care and education to First Nations and Métis people living with kidney disease while acknowledging Truth and Reconciliation and the Calls to Action. Sources of Information: This article describes how traditional Indigenous protocols and storytelling were woven into the Nîsohkamâtowak events, gathering of patient and family voices in writing and video format, and how this work led to a collaborative co-designed process that incorporates the Truth and Reconciliation: Calls to Action into kidney care and the benefits we have seen so far. The teachings of the 4 Rs—respect, reciprocity, responsibility, and relevance, were critical to ensuring that Nîsohkamâtowak reports and learning were shared with participants and the communities represented in this initiative. Methods: Group discussions and sharing circles were facilitated in several locations throughout northern and central Saskatchewan. Main topics of discussion were traditional medicines, residential schools impact, community and peer supports for kidney disease patients, and cultural safety education for health care providers. Key Findings: The general themes selected for improvement were education, support within the local community, traditional practices and cultural competency, and delivery of services. To address these gaps in kidney care, the following objectives were co-created with First Nations and Métis patients, families, and communities for Kidney Health to provide culturally appropriate education and resources, to ensure appropriate follow-up support to include strengthening connections to communities and other health authorities, to incorporate traditional practices into program design, and to ensure appropriate service delivery across the spectrum of care with a focus on screening and referral, which is strongly linked to coordination of care with local health centers. Implications: As a result of this work, the Kidney Health Community Program restructured the delivery of services and continues to work with Nîsohkamâtowak advisors on safety initiatives and chronic kidney disease awareness, prevention, and management in their respective communities. The Truth and Reconciliation and Calls to Action are honored to close the gaps in kidney care. Limitations: Nîsohkamâtowak is a local Kidney Health initiative that has the good fortune of having dedicated funding and staff to carry out this work. The findings may be unique to the First Nations and Métis communities and people who shared their stories. Truth and Reconciliation is an ongoing commitment that must be nurtured. Although not part of this publication, the effects of COVID-19 have made it difficult to further advance the Calls to Action, with more limited staff resources and the inability to meet in person as in the past.